Interaction of stilbene disulphonates with cloned K(ATP) channels. - Proks, P; Jones, P; Ashcroft, F (2001)
In this study, we tested the effects of the stilbene disulphonates DIDS and SITS on three different types of cloned K(ATP) channel (Kir6.2/SUR1, Kir6.2/SUR2A and Kir6.2DeltaC) heterologously expressed in Xenopus oocytes, with the aim of identifying the part of the channel which is involved in mediating disulphonate inhibition. We found that the inhibitory site(s) for these drugs lies within the Kir6.2 subunit of the channel, although its properties are further modulated by the sulphonylurea (SUR) subunit. In particular, SUR2A reduces both the rate and extent of block, by impairing the ability of DIDS binding to produce channel closure. The disulphonate-binding site interacts with the ATP inhibitory site on Kir6.2 because ATP is able to protect against irreversible channel inhibition by disulphonates. This effect is not mimicked by tolbutamide (at a concentration that interacts with Kir6.2) and is abolished by mutations that render the channel ATP insensitive. A number of point mutations in both the N and C termini of Kir6.2 reduced the extent and reversibility of channel inhibition by SITS. The results are consistent with the idea that residue C42 of Kir6.2 is likely to be involved in covalently linking of SITS to the channel. Other types of Kir channel (Kir1.1, Kir2.1 and Kir4.1) were also irreversibly blocked by DIDS, suggesting that these channels may share common binding sites for these stilbene disulphonates.